Experiences from the adverse drug event manager. (October 2022) - Horwitz, Henrik; Olsen, Rasmus H.; von Osmanski, Benedikte I.; Solem, Espen J.
Abstract : Summary: The current report briefly summarizes the experiences and statistics of the Adverse Drug Event Manager (ADEM) covering the Capital Region of Denmark, Denmark, during the period 1 January 2013 to 31 December 2020. During this 8-year period, the ADEM function has reported a total of 4262 adverse drug reactions (ADRs) to the Danish Medicines Agency, and of these, 141 had a fatal outcome (3.3%). The most commonly reported drugs were vaccines, antihypertensive agents, anticoagulants, and antiosteoporosis drugs. Fatal ADRs were predominantly related to anticoagulants. In 2020, the ADEM reported more than two-thirds of all ADRs for the Health Professionals in the Capital Region of Denmark. In addition to reporting ADRs, the ADEM has also had an extensive teaching and research activity and published a considerable number of studies on drug safety.